Induction of anti-cancer T cell immunity by in situ vaccination using systemically administered nanomedicines - Lynn, Geoffrey M; Laga, Richard; Jewell, Christopher M (Cancer letters, 2019)
Patients with inadequate anti-cancer T cell responses experience limited benefit from immune checkpoint inhibitors and other immunotherapies that require T cells. Therefore, treatments that induce de novo anti-cancer T cell immunity are needed. One strategy - referred to as in situ vaccination - is to deliver chemotherapeutic or immunostimulatory drugs into tumors to promote cancer cell death and provide a stimulatory environment for priming T cells against antigens already present in the tumor. However, achieving sufficient drug concentrations in tumors without causing dose-limiting toxicities remains a major challenge. To address this challenge, nanomedicines based on nano-sized carriers ('nanocarriers') of chemotherapeutics and immunostimulants are being developed to improve drug accumulation in tumors following systemic (intravenous) administration. Herein, we present the rationale for using systemically administrable nanomedicines to induce anti-cancer T cell immunity via in situ vaccination and provide an overview of synthetic nanomedicines currently used clinically. We also describe general strategies for improving nanomedicine design to increase tumor uptake, including use of micelle- and star polymer-based nanocarriers. We conclude with perspectives for how nanomedicine properties, host factors and treatment combinations can be leveraged to maximize efficacy.
Keywords: Pattern recognition receptor; Neoplasms; nanomedicína; Chemotherapeutic and immunostimulant; Cancer Vaccines; Nanoparticle and microparticle; T-lymfocyty; Immunotherapy; Nanomedicine; Adjuvants, Immunologic; Animals; lidé; Humans; adjuvancia imunologická; zvířata; imunoterapie; protinádorové vakcíny; nádory; T-Lymphocytes; Immunogenic cell death; Nanomedicine and biomaterials